2017
DOI: 10.1093/mnras/stx2195
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the redback millisecond pulsar binary 3FGL J0212.1+5320

Abstract: Linares et al. (2016) obtained quasi-simultaneous g , r and i -band light curves and an absorption line radial velocity curve of the secondary star in the redback system 3FGL J0212.1+5320. The light curves showed two maxima and minima primarily due to the secondary star's ellipsoidal modulation, but with unequal maxima and minima. We fit these light curves and radial velocities with our X-ray binary model including either a dark solartype star spot or a hot spot due to off-centre heating from an intrabinary sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 61 publications
5
31
0
Order By: Relevance
“…Using UVESPOP spectra we find that the line strength versus temperature relation of the metallic absorption lines in the 6000-6500 Å spectral range decreases with increasing temperature. Similarly, for the Hα absorption-line (Balmer), we find that the line strength increases with increasing temperature (Shahbaz et al 2017;Linares et al 2018). Therefore, we can compute the secondary star's metallic (K 2,Z ) or Balmer (K 2,H ) absorption-line radial velocity semi-amplitude.…”
Section: The Pulsar-state Radial Velocity Curvementioning
confidence: 69%
See 1 more Smart Citation
“…Using UVESPOP spectra we find that the line strength versus temperature relation of the metallic absorption lines in the 6000-6500 Å spectral range decreases with increasing temperature. Similarly, for the Hα absorption-line (Balmer), we find that the line strength increases with increasing temperature (Shahbaz et al 2017;Linares et al 2018). Therefore, we can compute the secondary star's metallic (K 2,Z ) or Balmer (K 2,H ) absorption-line radial velocity semi-amplitude.…”
Section: The Pulsar-state Radial Velocity Curvementioning
confidence: 69%
“…The moderate inclination angle of 54 • of the system (McConnell et al 2015) implies that the contrast between the observed spectral type at different orbital phases is reduced, which means that the observer always sees the heated inner face of the secondary star and thus the true spectral type of the secondary star is cooler. Simultaneous modelling of the optical light-and radial-velocity curves during the pulsar-state should reveal the true spectral type of the secondary star (Shahbaz et al 2017;Linares et al 2018)…”
Section: Spectral Type Changes Along the Orbitmentioning
confidence: 99%
“…The model, described in the following, has been successfully applied to LCs and RVCs of neutron star and black hole X-ray binaries (see Shahbaz et al 2000Shahbaz et al , 2003Shahbaz et al , 2017 for more details).…”
Section: Modelingmentioning
confidence: 99%
“…In determining the binary parameters, we use a Markov chain Monte Carlo (MCMC) method convolved with a differential evolution fitting algorithm (see Vrugt 2016;Shahbaz et al 2017). We use a Bayesian framework to determine our binary model parameters (Gregory 2005).…”
Section: Binary Parameters and Irradiationmentioning
confidence: 99%
“…At each phase of the model, we take the intensity-weighted velocity offset of each grid element from the center of mass as viewed by an observer, and combine it with an effective temperature-equivalent width relation for Mgb taken from Johansson et al (2010). This method is similar to that used by Shahbaz et al (2017) except that we do not set the equivalent widths of the elements heated beyond a certain point to zero, since this is not demanded by the data. Future spectroscopy with a larger telescope would allow improvements in the quality of the spectra that could show the need for additional modeling.…”
Section: Modeling the Radial Velocitiesmentioning
confidence: 99%